Impact of water stress on characteristics of soybean (Glycine max L.) inoculated with plant growth-promoting rhizobacteria at different growth stages - Balouei, Fatemeh (2016)
In this study, the effect of water stress on physiological characteristics and biochemical changes of soybean inoculated with PGPRs were considered. Soybean (Glycine max (L) Merr.) like most other legumes is able to fix nitrogen (N2), once it can establish a symbiotic relationship with soil nodulating bacteria belonging to the Rhizobiales order.This close association with N2-fixing bacteria makes possible for normal growth and development of legumes in nitrogen-poor soil under abiotic stresses. Soybean N2-fixation is a primary plant mechanism responsible for meeting plant-N demand during plant development. Nitrogen fixation is recognized as a drought-sensitive mechanism,especially in response to water deficit at different growth stages. Information about the effects of indigenous PGPRs (UPMB10 and UPMB12) and Bradyrhizobium (UPMR19) isolates as nitrogen fixer and their potential for soybean under drought, and their biological influence in tropical areas are still scarce; such data would be useful to provide information on availability of nitrogen for soybeans growth and development under abiotic stress particularly drought in tropical region. A factorial design experiment 1 was designed to determine the effect of water stress (well-watered, high and severe water stress) on nitrogenase activity, Malondialdehyde (MDA) and proline contents as well as Peroxidase (POX) activities of inoculated soybean with UPMB10,UPMB12 and UPMR19; and to inspect any potential of incremented tolerance of inoculated soybean to water stress. The average value of nitrogenase activity ranged from 22.25 to 51.3 nmol C2H4 plant-1 h-1. Highest amounts of MDA and proline were recorded at 92.98 μg groot-1 and 15.91 mg groot-1, respectively, and POX was 2.75 EU mg protein leaf-1 in un-inoculated soybean at severe stress level. In second experiment,the effect of water stress imposition at flowering (R2) and pod-filling (R6) stages (well-watered and high water stress) on MDA, proline and POX was designed in a factorial manner. The results showed values of mentioned parameters in ascending manner at flowering stage, but lightly decreasing at pod-filling and sharply diminishing at well-watered treatment. The results from experiment 2 showed that soybean exposed to high stress levels at pod-filling stage had best performance compared to flowering stage. In experiment 3, a factorial RCBD study was carried out to determine and investigate the most sensitive reproductive stage to stress during pod-filling (R6),either at the onset of pod (R3) stage or the onset of seed (R5) stage, as demonstrated by the nitrogenase enzyme production, MDA, proline and POX activities. The results showed that soybean at onset of pod stage is more sensitive to water stress compared to the onset of seed stage; and that, PGPRs+Bradyrhizobium (co-inoculated) protected the soybean plant more than inoculated and un-inoculated soybean under water deficit condition. Taken together, these results indicated that inoculated and co-inoculated of indigenous PGPRs and Bradyrhizobium with soybean are able to protect plant against oxidative damage generated by water stress due to their symbiosis that can directly alleviate the stress effect through nodule metabolism and N2-fixation.